(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Introduction: The growth of a country depends on the population, including both youth and old age, in which 48% of female will suffer from menopausal complications at one point of life. Acharyas have mention very few references on Rajonivritti. They have mentioned fifty years as the age of Rajonivritti. The concept behind the age of Rajonivritti is that Raja is byproduct of Rasadhatu which function better in Tarunavastha and its function reduces with age. Rajonivritti is a physiological process but when it causes discomfort either to mind or body it attains Vyadhisvarupa which may require medical interference. Sedentary lifestyle and unhealthy habits are one of the main causes for metabolic imbalance which leads to Rajonivruthi Lakshanas which manifest as Vyadhi. Method: This article has been made by reviewing various Samhitas, Nighantus, Sangrahas, Granthas to attain proper knowledge about the effect of Rasayana in improving the quality of life after menopause and in reducing Rajonivrithi Lakshana. Discussion: Acharya Sushruta contributed aging and diseases as the cause for the menopause. According to Jararog Chikitsasutra - Rasayana is the only way to combat symptoms associated with Jara. Result: By definition Rasayana, ‘Labhopayo hi shastanam Rasadinam Rasayanam’. As menopause is often associated with aging, it is signified by Dhatu Kshaya and Vata vitiation. Rasayana acts on the nutritional dynamics and rejuvenate the body on both physical and mental level. By proper administration of Rasayana therapy as preventive tool one can help in reducing the complication in menopause and can improve the quality of life. Hence the importance of Rasayana is highlighted here.